Genome sequencing and analysis of acropora gemmifera and pleuractics granulosa from Sabah costal waters - Lee, Dexter Jiunn Herng (2018)
Coral are marine invertebrates classified under the Anthozoa class of the Cnidaria phylum. In this study, Acropora gemmifera and Pleuractis granulosa from Sabah were morphologically identified and found to have green fluorescence (A. gemmifera and P. granulosa) and red fluorescence (P. granulosa) when exposed to blue and green wavelength LED lights respectively. The DNA for both A. gemmifera and P. granulosa, as well as the mRNA from A. gemmifera were extracted and sequenced using Illumina (Solexa) sequencers. The reads generated from the genome sequencing were quality filtered, binned and de novo assembled, resulting in assembled genome sizes of 686.45 Mbp (A. gemmifera) and 1.23 Gbp (P. granulosa) with mean coverages in excess of 80X. The assembled genome sizes may be overinflated due to the possible inclusion of contigs from other contaminating organisms, redundant contigs and misassemblies. Nucleotide variant calling and ploidy estimation suggest that both A. gemmifera and P. granulosa are diploid organisms. The mitochondrial genome assemblies for both A. gemmifera and P. granulosa resulted in two mitochondrial genomes with a size of approximately 18 kbp per genome (mean coverage in excess of 1,300X), with BLASTN alignment suggesting a high degree of similarity between both mitochondrial genomes with other mitochondrial genomes from the Acropora genus. Unsupervised rRNA predictions using the assembled genomes and their subsequent annotation suggests that the assembled genomes may contain contigs from non-coral organisms. A total of 131,730 mRNAs were predicted and assembled (reference-guided assembly) for A. gemmifera, while a total of 152,504 mRNAs were predicted for P. granulosa with the aid of mRNA sequencing data from Lobactis scutaria. These transcripts, as well as the pathways from the KEGG pathway analysis, will serve as a starting point for further investigations and possible commercialisation, though these transcripts and pathways would need to be experimentally validated beforehand.